Comparative antibiogram analysis of bacterial isolates from mastitic milk of cattle and buffalo in Haryana - Rahul Yadav; Pankaj Kumar; Anand Prakash; Bhanot, Vandna (Indian Journal of Dairy Science, 2024)
Mastitis causes huge economic losses to dairy industries worldwide. It is caused by various microorganisms, of which bacterial etiology is primarily important. Both Gram-positive and Gram-negative bacteria are involved in causation of disease. In the present study, 8561 milk samples from both cattle and buffalo combined were tested and occurrence of mastitis was recorded in 72.73 % (n = 6227/8561) milk samples. Occurrence of mastitis was non–significantly (p>0.05) higher in cattle (86.31%) than buffaloes (66.97%). California Mastitis Test (CMT) showed significantly (p<0.05) lower prevalence of mastitis compared to the culture examination statistically. By CMT analysis, buffalo had a significantly (p<0.05) lower percentage of mastitis positivity than cattle. Whereas, culture examination revealed that both cattle and buffalo exhibited a high prevalence of mastitis, with 97.75% and 98.15% positive samples, respectively. Gram-positive bacteria were found as the predominating etiological agents causing mastitis in 62.62% samples followed by Gram-negative bacteria (24.54%) from milk samples of cattle and buffalo combined. Mixed infection of both Gram-positive and Gram-negative bacteria was found in 10.50% milk samples. Over all 2970 samples from cattle (n = 1071) and buffalo (n = 1899) were subjected for culture examination and antibiotic sensitivity assay. The findings from the present study revealed variations in antibiotic sensitivity across different districts. The district of Bhiwani consistently showed lower sensitivity rates for most antibiotics compared to the other districts. Overall, chloramphenicol, enrofloxacin, gentamicin, ciprofloxacin, cefoperazone and levofloxacin were most sensitive antibiotic across all districts. Amoxicillin + Clavulanic acid and ampicillin were most resistant antibiotics in all districts.